Patterns in hydraulic architecture from roots to branches in six tropical tree species from cacao agroforestry and their relation to wood density and stem growth - Kotowska, Martyna M.; Hertel, Dietrich; Rajab, Yasmin Abou; Barus, Henry; Schuldt, Bernhard (Frontiers in Plant Science, 2015)
For decades it has been assumed that the largest vessels are generally found in roots and that vessel size and corresponding sapwood area-specific hydraulic conductivity are acropetally decreasing towards the distal twigs. However, recent studies from the perhumid tropics revealed a hump-shaped vessel size distribution. Worldwide tropical perhumid forests are extensively replaced by agroforestry systems often using introduced species of various biogeographical and climatic origins. Nonetheless, it is unknown so far what kind of hydraulic architectural patterns are developed in those agroforestry tree species and which impact this exerts regarding important tree functional traits, such as stem growth, hydraulic efficiency and wood density. We investigated wood anatomical and hydraulic properties of the root, stem and branch wood in Theobroma cacao and five common shade tree species in agroforestry systems on Sulawesi (Indonesia); three of these were strictly perhumid tree species, and the other three tree species are tolerating seasonal drought. The overall goal of our study was to relate these properties to stem growth and other tree functional traits such as foliar nitrogen content and sapwood to leaf area ratio. Our results confirmed a hump-shaped vessel size distribution in nearly all species. Drought-adapted species showed divergent patterns of hydraulic conductivity, vessel density and relative vessel lumen area between root, stem and branch wood compared to wet forest species. Confirming findings from natural old-growth forests in the same region, wood density showed no relationship to specific conductivity. Overall, aboveground growth performance was better predicted by specific hydraulic conductivity than by foliar traits and wood density. Our study results suggest that future research on conceptual trade-offs of tree hydraulic architecture should consider biogeographical patterns underlining the importance of anatomical adaptation mechanisms to environment.